The Relationship between Pupil Diameter and Other Measures of Opioid Withdrawal During Naloxone Precipitated Withdrawal - Bergeria, Cecilia L. (Drug Alcohol Depend, 2019)
BACKGROUND: Understanding mechanisms of physiological opioid withdrawal symptoms can inform treatment strategies. This secondary analysis evaluated the association between mydriasis (dilated pupils), a commonly-assessed opioid withdrawal metric, with self-and observer-rated opioid withdrawal severity. METHOD: Ninety-five participants with opioid physical dependence were stabilized with morphine before receiving an injection of the opioid antagonist naloxone to precipitate withdrawal. Pupil diameter, the Subjective Opiate Withdrawal Scale (SOWS), and the Clinical Opiate Withdrawal Scale (COWS) were collected at baseline and in 15-minute intervals for 120 minutes following naloxone administration. Pearson product-moment correlations and linear regressions characterized the relationships between pupil measurements (baseline and peak naloxone-induced) and self-and observer-rated measures of withdrawal. Repeated-measures ANOVAs tested whether self and observer-rated withdrawal severity corresponded to unique patterns in pupil changes. RESULTS: Baseline pupil diameter significantly correlated with SOWS and COWS peak scores. Peak naloxone-induced pupil diameter significantly correlated with SOWS scores only. Peak changes in pupil from baseline did not correspond to peak changes in self-and observer-rated withdrawal scales. CONCLUSIONS: This study suggests that pupil diameter measurements were more closely associated with acute opioid withdrawal severity than changes in pupil diameter. Prospective research examining the mechanisms underlying the relationship between pupil diameter and opioid withdrawal severity are warranted.